Effects of Nb/Ti additions and heat treatment on the microstructure evolution and hardness of as-cast and directionally solidified NiAl–Cr(Mo) alloy - Zhao Shang; Qianwei Zhang; Jun Shen; Haiqiang Bai; Xiaowan Dong; Wenfang Bai; Lisheng Zhong; Gang Liu; Yunhua Xu (Journal of Materials Research and Technology, 2021)
The effects of the addition of Nb and Ti and heat treatment on the microstructure evolution and hardness of the as-cast and directionally solidified NiAl–Cr(Mo) alloy were studied. Nb mainly solubilizes in the Cr(Mo) phase while Ti basically solubilizes in the NiAl phase. Precipitated phases of Cr2Nb and Ni2AlTi are formed and mainly distributed at the cell boundary. With the increasing Nb content, the primary Cr(Mo) phase increases significantly and does not show dendritic morphology. The eutectic coupled growth is suppressed and the lamellar microstructure becomes irregular. Fully eutectic microstructure with no primary Cr(Mo) phase is obtained in the directionally solidified NiAl–Cr(Mo)–Nb and NiAl–32Cr–6Mo–1Ti–1Nb alloys while dendrites + eutectic is observed in the directionally solidified NiAl–32Cr–6Mo–3Ti–3Nb alloy. After heat treatment, Nb and Ti are redistributed. The eutectic microstructure becomes relatively uniform and the precipitated phases become fine and dispersed. The addition of Nb and Ti can increase the hardness of the alloy due to the solid solution strengthening and precipitation strengthening. As the Nb content increases, the hardness further increases. The hardness of the directionally solidified alloys is higher than the as-cast alloys attributing to the regular microstructure. After heat treatment, the hardness of the all alloys decreases due to the varying microstructure morphology and phase distribution, especially the coarsening of NiAl precipitates and the existence of dislocations in Cr(Mo) phase.